2014
DOI: 10.1007/s11010-014-2259-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide augments the uptake of oxidized LDL by up-regulating lectin-like oxidized LDL receptor-1 in macrophages

Abstract: There is a growing body of evidence supporting an intimate association of immune activation with the pathogenesis of cardiovascular diseases, including atherosclerosis. Uptake of oxidized low-density lipoprotein (oxLDL) through scavenging receptors promotes the formation of mature lipid-laden macrophages, which subsequently leads to exacerbation of regional inflammation and atherosclerotic plaque formation. In this study, we first examined changes in the mRNA level of the lectin-like oxLDL receptor-1 (LOX-1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…Dysfunctional HDL that is known to be oxidized [1417], has previously been shown in vitro to directly influence monocyte [40] and dendritic cell [41] function in systemic inflammatory states [40, 41]. Lipoproteins bind endotoxin which is present in viremic HIV-infected individuals, acts synergistically with LDL ox [42] and may contribute to immune activation [1]. Thus, further studies are needed to elucidate whether oxidized lipoproteins, through effects on immunity and endotoxin, may contribute to immune activation in viremic HIV infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional HDL that is known to be oxidized [1417], has previously been shown in vitro to directly influence monocyte [40] and dendritic cell [41] function in systemic inflammatory states [40, 41]. Lipoproteins bind endotoxin which is present in viremic HIV-infected individuals, acts synergistically with LDL ox [42] and may contribute to immune activation [1]. Thus, further studies are needed to elucidate whether oxidized lipoproteins, through effects on immunity and endotoxin, may contribute to immune activation in viremic HIV infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is expressed in the aorta of hypertensive, diabetic and hyperlipidemic animals [18], and it is up-regulated in early human atherosclerotic lesions [19]. These results suggest that LOX-1 plays an important role in atherogenesis, by internalizing and degrading ox-LDL, and in inflammatory responses in vivo, raising cellular ox-LDL uptake [20]. The endothelial activation and dysfunction induced by ox-LDL is a key event in the pathogenesis of inflammation and atherosclerosis.…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, we could not find significant gene regulation of aggrecanases and did not detect MMP-expression (data not shown), but we previously showed that monocytes can develop a pro-inflammatory phenotype after training by oxLDL 35 . Furthermore, inflammatory factors such as toll-like receptor 4 ligands (e.g., S100A8) could change receptor balances in the synovium, changing affinity of different cell types to take up oxLDL 36 .…”
Section: Discussionmentioning
confidence: 99%